Analisis Semiotika Representasi Nilai-nilai Islam Dalam Tayangan Film Ayat-Ayat Cinta - Riski, Israq; Monang, Sori; Batubara, Abdul Karim (Journal of Educational Research and Humaniora (JERH), 2024)
Film is one of mass media having responsibility to decrease and increase education like radio, television and newspapers as well. The form of religious values can be conveyed through messages in the film. This paper contains religious values in the film Ayat-Ayat Cinta. It uses semiotic analysis method by Pierce. Therefore, religious values that are delivered in the film Ayat-Ayat Cinta can be revealed. Firstly, the researcher chooses some scenes in the film Ayat-Ayat Cinta. Then, those scenes are analyzed through denotative, connotative, and myth meaning. Basically, there are many things which can be interpreted in a film. Of course, it must be suitable with the context rising in the scenes in order to result matters pertaining to meaning and understanding of messages. This is a qualitative research. It considers meaning as the main attention. In addition, this research only develops collecting facts. Thus, they are analyzed without doing hypothesis experiment. The researcher chooses the film Ayat-Ayat Cinta because there are many deviations happening today, especially for teenagers. It seems that Ayat-Ayat Cinta bringing freshness in order to give education and study about religious values. After a long process up to analysis, it results that Ayat-Ayat Cinta having religious messages which reveal in the scenes.